Institutional Responses to the COVID-19 Pandemic: A Multi-Site Mixed-Methods Study of Philippine Hospitals - Eliza B. Ayo; Paul C. Brigino; Alfredo D. Padua Jr; Nathaniel Francis G. Precilla; Celia L. Verano; Angelita Alonzo (Future Science / FSH-PH Publications, 2026)
The COVID-19 pandemic exposed profound structural vulnerabilities within the Philippine hospital system while simultaneously revealing remarkable adaptive capacities among frontline healthcare workers and institutional leaders. This mixed-methods, multi-site study examined how 34 Philippine hospitals of varying types, levels, and geographic locations responded to the pandemic. One key informant per hospital represented by a healthcare worker with direct institutional experience of the pandemic that served as the institutional respondent, making each response a hospital-level account. Using a structured survey questionnaire administered in January 2026, the study collected demographic and institutional profile data, along with qualitative responses to 32 open-ended items spanning eight thematic sections that were analyzed and reported across four consolidated domains: policy implementation and governance; operational response and resource management; workforce management and leadership; and lessons learned and policy recommendations. Descriptive statistics and frequency distributions were employed for quantitative profile variables, while thematic analysis was applied to qualitative responses. Because the data were gathered retrospectively, several years after the events of 2020–2022, the findings are interpreted with explicit attention to recall limitations. Findings reveal that hospitals rapidly adapted national directives from the Department of Health (DOH) and the Inter-Agency Task Force (IATF) into local protocols, though frequent policy revisions, resource scarcity, and uneven institutional capacity consistently challenged implementation. Tertiary-level and urban hospitals demonstrated faster adoption of digital tools and infection prevention measures, while rural and Local Government Unit (LGU)-managed facilities relied more heavily on community partnerships and improvised protocols.